A hierarchy of finite state machines as a scenario player in interactive training of pilots in flight simulators - Bach, Małgorzata; Werner, Aleksandra; Mrozik, Magda; Cyran, Krzysztof A. (Zielona Góra: Uniwersytet Zielonogórski)
The paper presents the concept of a control unit, i.e., a scenario player, for interactive training pilots in flight simulators. This scenario player is modelled as a hierarchy of finite state machines. Such an approach makes it possible to separate the details of an augmented reality display device which is used in training, from the core module of the system, responsible for contextual organization of the content. Therefore, the first contribution of this paper is the mathematical model of the scenario player as a universal formulation of the self-trained control unit for interactive learning systems, which is applicable in a variety of situations not limited solely to flight simulator related procedures.
Keywords: Bayesian inference; deterministic Moore machine; flight simulator; hierarchy of finite state machines; scenario player